Functioning of the morphological and syntactic method in the Arabic computer sublanguage. (Journal of Oriental Studies, 2016)
The article describes the morphological and syntactic method of term formation in Arabic computer sublanguage as one of theleast productive ways in terminology. The material is based on statistics, the present number of terms identified in the result of study.
Keywords: allipsis; Abbreviation; morphological-syntactical